2006
DOI: 10.1088/0960-1317/16/10/037
|View full text |Cite
|
Sign up to set email alerts
|

Electroplated nickel micromachined probes with out-of-plane predeformation for IC chip testing

Abstract: This paper presents a new type of electroplated nickel micromachined probe with out-of-plane predeformation for next generation integrated circuit (IC) chip testing probe card applications. The probe card was fabricated using silicon bulk micromachining, titanium (Ti) deposition, nickel (Ni) electroplating and laser scribing processes. We use the effect of the residual stresses of thin-film deposition on flexible micromachined probes to produce a large out-of-plane predeformation and combine the post-electropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…4(d)]. A submicrometer-thick Ti film was then deposited by thermal evaporation as an adhesive layer and used as a seed layer because it has a large residual For the fabrication of each probe electrode, the throughsilicon via technique with inductively coupled plasma dry etching and electroplating process have been used by many studies to accomplish the interconnections embedded in the silicon substrate [14]- [16], and laser scribing has also been used to achieve the electrical separation of the electroplated Ni layer [10], in which the through-silicon via and electroplating process achieve a fine pitch and high-density multiarray interconnections with greater electrical performance and the laser machining offers great performance at low cost and a high yield. The minimum kerf width was maintained at less than 10 μm for scribing depths of 25 μm large.…”
Section: B Fabrication Processmentioning
confidence: 99%
See 2 more Smart Citations
“…4(d)]. A submicrometer-thick Ti film was then deposited by thermal evaporation as an adhesive layer and used as a seed layer because it has a large residual For the fabrication of each probe electrode, the throughsilicon via technique with inductively coupled plasma dry etching and electroplating process have been used by many studies to accomplish the interconnections embedded in the silicon substrate [14]- [16], and laser scribing has also been used to achieve the electrical separation of the electroplated Ni layer [10], in which the through-silicon via and electroplating process achieve a fine pitch and high-density multiarray interconnections with greater electrical performance and the laser machining offers great performance at low cost and a high yield. The minimum kerf width was maintained at less than 10 μm for scribing depths of 25 μm large.…”
Section: B Fabrication Processmentioning
confidence: 99%
“…Based on the complete version of Stoney's equation and the material properties of the structure layers, as well as the measured radius of curvature, the calculated residual stress of Ti film was 923 MPa [17]. A detailed report on the residual stress effect of Ti on micromachined beams is available as our previous work [10]. However, the measured radius of curvature of the deflected single-layer SiO 2 cantilever, before Ti deposition, was about 5.3 mm, and the calculated residual stress was only 8.36 MPa [18], [19].…”
Section: A Probe Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Various types of probe cards are manufactured, including epoxy, blade, vertical, array, and microspring types [1][2][3][4][5][6][7][8]. The emerging microspring microelectromechanical system (MEMS) probe card is beginning to dominate wafer testing [9][10][11][12]. These cards can achieve fine-pitch, multi-device-under-test (multi-DUT) performance and one-or minimum-touchdown wafer testing.…”
Section: Introductionmentioning
confidence: 99%
“…Hantschel et al [10] reported on connectors using stress mismatch caused by two metal beam layers. Jing et al [11] and Tsou et al [12] reported on probe tips that incorporated electroplated Ni. However, most of them are difficult to make connectors uniformly because of different stress of beam layers.…”
Section: Introductionmentioning
confidence: 99%